Improved myocardial lactate extraction after propranolol in coronary artery disease: effected by peripheral glutamate and free fatty acid metabolism. Issue 2 (February 1986) - Nielsen, T T; Bagger, J P; Thomassen, A
Abstract : Ten patients with chronic effort angina and coronary artery disease (luminal diameter reduction greater than 75%) were stressed by atrial pacing (140 beats/minutes) before and 15 minutes after intravenous propranolol (mean dose 7.4 mg). Myocardial substrate exchange of oxygen, blood lactate, plasma free fatty acids, citrate, glucose, glutamate, and alanine as well as coronary sinus blood flow were measured. Coronary sinus blood flow, oxygen consumption, and systemic haemodynamics did not change after propranolol. Propranolol did not influence arterial lactate concentration, and it reduced the arterial concentration of free fatty acid by 37% and increased that of glutamate by 21%. During pacing myocardial lactate extraction increased in all 10 patients; in two lactate release was converted to lactate uptake. Propranolol reduced free fatty acid uptake and increased glutamate uptake during pacing. For both substances the changes in aortocoronary sinus differences or in uptake or both correlated positively with the changes in their delivery to the heart from extracardial sources (arterial concentrations/loads). In the unstressed state before pacing, aortocoronary sinus lactate differences correlated inversely with free fatty acid differences and positively with those of glutamate. During pacing the relation between lactate and glutamate differences remained positive while the inverse correlation between lactate and free fatty acid differences was lost. Myocardial citrate release was halved during pacing and recovery. Propranolol did not influence alanine or glucose exchanges. An improved myocardial lactate extraction after propranolol administration may be secondary to decreased free fatty acid uptake or increased glutamate uptake or both. In the unstressed state both mechanisms may be of importance. During pacing induced ischaemia, increased glutamate uptake is more likely than reduced free fatty acid uptake to be the mechanism responsible for the improvement in myocardial lactate extraction. The propranolol mediated alterations in myocardial substrate exchanges may reflect the extracardial effects of the drug.